Nanofluids in Solar Thermal Collectors: Review and Limitations - Ifeoluwa Wole-osho (14151057) (2022)
Solar thermal collectors are systems that allow for the use of solar energy in thermal applications. These collectors utilize a heat transfer fluid to transport absorbed solar radiation to applications where they are needed. Scientists in a bid to improve the conversion efficiency of solar collectors have suggested different collector designs and improved collector materials. Over the last 25 years, the study of nanofluids and their applications have revolutionized material science, and nanotechnology has found applications in improving solar collector materials. This article reviews the impact of different nanomaterials on the efficiency of solar collectors. The study also outlines the limitations of applying nanofluids and discusses the long-term challenges of their application to solar collectors. Nanofluids have the potential to improve the overall efficiency of most solar collectors, however, the full potential of nanofluids in heat transfer applications cannot be completely achieved until some of the questions regarding hysteresis, stability, and the overall predictability of nanofluids are answered. Other Information Published in: International Journal of Thermophysics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10765-020-02737-1